Pilihan Konsumen Dalam Menggunakan Fitur Go-Food: Variabel Kegunaan sebagai Moderator - Ni Putu Yuliana Ria Sawitri, Luh Erynayati, Made Ayu Desy Geriadi, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
The purpose of this study was to see the useful role in mediating the effect of choice on intention to use. This research was conducted at the Faculty of Economics and Business, Ngurah Rai University, located on Jalan Padma Penatih, Denpasar, Bali Province. The sample used in this study used a random sampling technique, where the respondents were students. The number of samples used was 100 people. The analysis technique used is the structural equation modeling (Structural Equation Modeling - SEM) based on the variant known as the Partial Least Square (PLS).The results showed that choice has a positive and significant effect on perceived benefits. The perceived usefulness has a positive and significant influence on the intention to use the Go-Food feature on the Gojek application. The choice of food variations has a positive and significant effect on the intention to use the Go-Food feature on the Gojek application. The perceived usefulness is able to mediate a positive and significant influence on the intention to use the Go-Food feature on the Gojek application.